Strategi Industri Dasar Dan Strategi Orientasi - Ayunda Febri Kinanti; Muhammad Syahrul Maulana; Muhammad Yasin (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This research aims to analyze the differences and similarities between basic industrial strategy and orientation strategy in the context of business development. A basic industrial strategy covers the general approaches used by companies to operate in a particular industry, including competitive analysis, supply chain, and risk management. On the other hand, onboarding strategy focuses on adjusting and adapting business strategies to changes in the external environment, such as technology, regulations and consumer preferences. Through literature studies and case analysis, this research finds that the integration of these two strategies can provide significant competitive advantages for companies. The success of implementing a basic industrial strategy is greatly influenced by the company's ability to adapt its orientation strategy according to market dynamics and the business environment. This research concludes that a deep understanding of these two types of strategies and their appropriate implementation can help companies improve their business performance and sustainability.